Nitrogen effect on amino acid composition in leaf and grain of japonica rice during grain filling stage. (July 2015) - Zhao, Yanling; Xi, Min; Zhang, Xincheng; Lin, Zhaomiao; Ding, Chengqiang; Tang, She; Liu, Zhenghui; Wang, Shaohua; Ding, Yanfeng
Abstract: This paper reports the effect of nitrogen on amino acid composition of leaf and grain for japonica rice during the grain filling stage, using pot experiments with three N rate treatments. Dynamic changes of free amino acids (FAA) and protein amino acids (PAA) in leaves and grains were monitored. Results showed that FAA in leaves decreased with the progress of grain filling. FAA in grains increased at first 14 days after anthesis and then decreased to a nearly constant level. PAA in leaves showed a diminishing trend as leaf senesced after anthesis. Conversely, PAA in grain exhibited an increasing trend with the progress of grain filling. N had significantly positive effect on contents of FAA and PAA in leaves and grains. There was no obvious trend of the variation of FAA in leaves and grains with N rates. PAA in leaves was more sensitive to N fertilization. By contrast, PAA in grains was more stable across N rates, especially at the late stage of grain filling. In addition, composition of leaf PAA was different from that of grain, indicating the reconstruction of amino acids during the process of translocation of N compounds from leaves to grains. Highlights: We investigated effect of nitrogen (N) on leaf and grain amino acid composition. Composition of leaf protein amino acids (PAA) was different from that of grain. N showed significant effect on PAA composition. PAA in leaves was more sensitive to N fertilization. PAA in grains was more stable across N treatments.